An experimental and numerical study of turbulent heat transfer enhancement for graphene nanofluids produced by pulsed discharge. (November 2022) - Fujimoto, Kotaro; Shibata, Aima; Torii, Shuichi
Highlights: Time and cost-effective production of graphene nanofluids by pulsed discharge is tried and tested. A new two-step method for producing graphene nanofluids has been developed. Graphene nanofluids generated by pulsed discharge and ultrasound, like other graphene nanofluids, have high turbulent heat transfer performance (35% higher than water). The numerical results show considerable increase in turbulent kinetic energy (8%) and velocity gradients near the wall due to physical interaction between continuous phase(water) and dispersed phase (graphene nano-particles). The exchange of momentum and energy due to the movement of particles is considered as a cause-and-effect relationship between the aggregation of particles and the change in physical quantities in the continuous phase. Abstract: Developing production methods for graphene nanofluids that can produce them in large quantities at once in a short time and at a low cost will contribute to the development of a wide range of industries that use nanofluids, and understanding their properties through mathematical modeling and experiments will lead to the development of new nanofluids. In this study, the new production method of graphene nanofluids is proposed and experimental and numerical investigations of the turbulent heat transfer performance of graphene nanofluids in a horizontal circular tube subjected to constant heat flux are conducted. The experimental investigation is conducted to evaluate the turbulent heat transfer performance of graphene nanofluids which are made by a new method using pulsed discharge and to compare them with numerical results. In the numerical investigation, the finite volume method with a Realizable k-ε model and Two-layer model is employed to solve the continuity, momentum, and energy conservation in two-dimensional domains. The Lagrangian two-phase model is applied to consider the physical interaction between the dispersed phase and continuous phase. In this model, the particles are tracked in a Lagrangian manner and coupled with the Eulerian flow description. Since the computational burden would be tremendous if individual nanoparticles were tracked in a Lagrangian manner, we defined a cluster of particles, called a parcel and treated it statistically. This concept of parcels allowed the average behavior of nanoparticles to be established as an analytical parameter. As a result, graphene nanofluids are not produced by pulsed discharge alone but are successfully produced by applying ultrasonic. Experimental investigations show a 33% increase in the Nu number of graphene nanofluid produced by pulsed discharge compared to water as the flow velocity increased. Numerical investigations confirm changes in the properties (Turbulent kinetic energy, Velocity distribution, Temperature distribution) of the continuous phase due to physical interactions between the dispersed and continuous phases. It is also shown that these changes contribute to the improved turbulent heat transfer performance of the nanofluid and that the aggregation of particles into the center of the tube is responsible for these changes.